The Manhattan Bugle - Linda Brooks-Pilling; Amos I.T. Chang (Oz, 1981)
This project for a medium sized newspaper plant was the terminal project in a semester focusing on the Manhattan Industrial Park. The park is zoned to allow light industrial, commercial and office development…